Interoceptive awareness: MBSR training alters information processing of salience network - Guu, Shiao-Fei; Chao, Yi-Ping; Huang, Feng-Ying; Cheng, Yu-Ting; Ng, Hei-Yin Hydra; Hsu, Chia-Fen; Chuang, Chun-Hsiang; Huang, Chih-Mao; Wu, Changwei W. (Frontiers in Behavioral Neuroscience, 2023)
Mindfulness refers to a mental state of awareness of internal experience without judgment. Studies have suggested that each mindfulness practice may involve a unique mental state, but the underlying neurophysiological mechanisms remain unknown. Here we examined how discrepancies in brain-network organizations stem from distinct mindfulness practices during mindfulness-based intervention shape brain functionality and alter behaviors. Specifically, we investigated the functional alterations of the salience network (SN) using functional magnetic resonance imaging (fMRI) among the two interoceptive mindfulness practices – breathing and body scan – associated with interoceptive awareness in fixed attention and shifted attention, respectively. Long-distance functional connectivity (FC) and regional homogeneity (ReHo) approaches were applied to measure distant and local neural information processing across various mental states. We hypothesized that mindful breathing and body scan would yield a unique information processing pattern in terms of long-range and local functional connectivity (FC). A total of 18 meditation-naïve participants were enrolled in an 8-week mindfulness-based stress reduction (MBSR) program alongside a waitlist control group (n = 14), with both groups undergoing multiple fMRI sessions during breathing, body scan and resting state for comparison. We demonstrated that two mindfulness practices affect both the long-distance FCSN and the local ReHo, only apparent after the MBSR program. Three functional distinctions between the mindfulness practices and the resting state: (1) distant SN connectivity to occipital regions increased during the breathing practice (fixed attention), whereas the SN increased connection with the frontal/central gyri during the body scan (shifting attention); (2) local ReHo increased only in the parietal lobe during the body scan (shifting attention); (3) distant and local connections turned into a positive correlation only during the mindfulness practices after the MBSR training, indicating a global enhancement of the SN information processing during mindfulness practices. Though with limited sample size, the functional specificity of mindfulness practices offers a potential research direction on neuroimaging of mindfulness, awaiting further studies for verification.